Insights into Haemophilus macrolide resistance: A comprehensive systematic review and meta-analysis. - Irfan Ahmad; Aziz Kubaev; Ahmed Hussein Zwamel; Roopashree R; Lalji Baldaniya; Jaswinder Kaur; Bindu Rani; Masoumeh Beig (PLoS Neglected Tropical Diseases)
Background Haemophilus spp., particularly Haemophilus influenzae, are major global pathogens causing various infections. Macrolides are crucial in treating these infections, but rising resistance to macrolides in Haemophilus spp. highlights the growing threat of antimicrobial resistance (AMR). Objective This study aims to assess the prevalence of macrolide resistance in Haemophilus spp, across different global regions. Methods A systematic literature search was conducted across PubMed, Embase, Web of Science, and Scopus databases from May 2015 to December 2023 to identify studies on macrolide resistance in Haemophilus spp. The review included English-language full-text articles that reported resistance proportions and sample sizes. Study quality was assessed using the JBI Critical Appraisal Tool. Statistical analysis was performed using a random-effects model using the metafor package in R. Results A total of 10,114 articles were retrieved, and after a comprehensive evaluation, 15 studies (from 19 reports) met the eligibility criteria for inclusion in this systematic review and meta-analysis. Most studies (eight reports from three countries) focused on clarithromycin susceptibility, revealing a pooled prevalence of 7.2%. High heterogeneity was observed for azithromycin (I² = 96.31%, p < 0.001). Azithromycin resistance was higher than clarithromycin, with a resistance rate of 9.3% (nine reports), while erythromycin resistance was significantly higher at 79% (four reports). Subgroup analysis revealed significant variations in resistance prevalence based on geographic location and continent for azithromycin, erythromycin, and clarithromycin. Additionally, notable differences were observed in resistance rates depending on antimicrobial susceptibility testing (AST) methods and AST guidelines for both azithromycin and erythromycin. Clarithromycin resistance increased from 0.7% (2015-2019) to 12.6% (2020-2023). Conclusion The study underscores the significant challenges of macrolide resistance in treating Haemophilus spp. infections. Additionally, ongoing surveillance of resistance patterns and exploring contributing factors are crucial to enhancing treatment effectiveness.